PENGGUNAAN KARET ALAM UNTUK MENINGKATKANSIFAT FISIK ASPAL KERAS - Iriansyah. AS (Jurnal Jalan-Jembatan, 2005)
In order to improve efficiency on road infrastructure, it is necessary to apply various appropriate alternatives and innovation of road material technology, which has connection to the road fungction, traffic load and road location. In the meanwhile, it is often found earlier road distress before it reaches an ideal age service, especially in the areas which have high traffic volume and traffic load. There are many factor of earlier road deterioration, those are the wrong use of asphalt type, by using low penetration asphalt which lead to road cracking, while using high penetration with softening point and high temperature of road surface often causes plastic flow. One of the alternative to handle it by giving natural rubber into asphalt, to improve its phycical properties and qualities. Therefore it is beneficial to use natural rubber, not only because Indonesia is one of the biggest natural rubber production, but also improving natural rubber consumtion. In this research, the natural rubber used as additive substance are latex, sticky latex and Rubber Sir 20, the natural rubber resulted from domestic plantation, which has gond quality and relatively cheap for road. Laboratory test at Reseach and Development Centre for Road Infrastruc ture only limited to physical properties of hard asphalt penetration 60 by adding various rubber contents 1 – 5% of asphalt weight. Increasing small amount of natural rubber into asphalt penetration 60 is able to improve its physical properties by decreasing pene tration and softening point increasing. This is the fact that rubber asphalt is more resistance to high temperature, however, ductility value is not change means asphalt has high elastic properties